REGULASI DAN IMPLEMENTASI PENGELOLAAN PCB (POLYCHLORINATED BIPHENYLS) DI INDONESIA - Paramita, Dianing; Rahardiansyah, Trubus (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The management of Polychlorinated Biphenyls (PCB) in Indonesia faces significant challenges related to the implementation of existing environmental regulations. Although there are rules governing the use and disposal of PCB, there are still several obstacles in law enforcement and public awareness regarding the dangers of this substance. This study aims to analyze the effectiveness of current regulations and provide recommendations to enhance the sustainable management of PCB, focusing on improving coordination among government agencies, public education, and strengthening monitoring systems to prevent further pollution.Keywords: PCB, PCB Management, Polychlorinated Biphenyls.